2016
DOI: 10.1111/pace.12953
|View full text |Cite
|
Sign up to set email alerts
|

The Right to Left Atrial Volume Ratio Predicts Outcomes after Circumferential Pulmonary Vein Isolation of Longstanding Persistent Atrial Fibrillation

Abstract: The ratio of the RAVI to LAVI on CT may be a useful predictor of clinical outcomes after CPVI of LSP-AF. LSP-AF patients with a less predominant right atrial enlargement relative to the left atrial enlargement may be good candidates for successful treatment with CPVI alone as the ablation strategy for LSP-AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…Although the enlargement of atrial size between the LA and RA in patients with paroxysmal AF is similar in magnitude, physicians have focused more on the increase in LA size than the RA. However, recent clinical studies demonstrated that RA enlargement was independently associated with AF recurrence after catheter ablation in patients with paroxysmal AF and also persistent AF . Simultaneous evaluation of RA and LA size is important for AF management.…”
Section: Discussionsupporting
confidence: 47%
“…Although the enlargement of atrial size between the LA and RA in patients with paroxysmal AF is similar in magnitude, physicians have focused more on the increase in LA size than the RA. However, recent clinical studies demonstrated that RA enlargement was independently associated with AF recurrence after catheter ablation in patients with paroxysmal AF and also persistent AF . Simultaneous evaluation of RA and LA size is important for AF management.…”
Section: Discussionsupporting
confidence: 47%
“…RA diameter predicts ablation outcomes only in patients with paroxysmal AF and concurrent LA enlargement. In recent years, Sasaki et al reported that the ratio of RA volume index to LA volume index is a risk factor for AF recurrence 10 . This previous study enrolled patients with only persistent AF.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that RA diameter can affect the early recurrence of AF after ablation 8 . Others have also reported that RA anatomical remodeling can predict the success of AF cardioversion, 9 and the ratio of the RA volume index to the LA volume index is a risk factor for AF recurrence 10 . However, it is unclear to what extent RA contributes to the ablation outcome in the general population with AF.…”
Section: Introductionmentioning
confidence: 99%
“…A JPVI és BPVI monalis vénaizoláción átesett betegekben (34). A JPVI miatt operált betegekben a szupraventrikuláris aritmiák prediktorának bizonyult (35).…”
Section: A Jobb Pitvar Méretének Klinikai Jelentőségeunclassified